Integrating Constituents Absorbed into Blood, Network Pharmacology, and Quantitative Analysis to Reveal the Active Components in Rubus chingii var. suavissimus that Regulate Lipid Metabolism Disorder - Jiang, Man-jing; Huang, Wan-fang; Huang, Shuai; Lu, Yi-xiang; Huang, Yong; Du, Pei-lin; Li, Yao-hua; Fan, Lan-lan (Frontiers in Pharmacology, 2021)
Rubus chingii var. suavissimus (S. K. Lee) L. T. Lu (RS) –a sweet plant also known as Tiancha distributed in the south of China where it is used as beverage– recently gained extensive attention as adjuvant therapy of diabetes and hypertension. Although pharmacological studies indicate that RS has beneficial effects in regulating lipid metabolism disorder characteristics, the active chemicals responsible for this effect remain unclear. The present study aims to predict the effective substances of RS on regulating lipid metabolism disorders through analysis of the chemical profile of RS, the absorbed prototype components in rat plasma, and network pharmacology. Also, an UPLC method able to quantify the screened potential effective chemicals of RS products was established. First, a total of 60 components –including diterpene, triterpenoids, flavonoids, polyphenols, and lignans– were systematically characterized in RS. Of those, 50 compounds were detected in plasma of rats administered RS extract. Through network pharmacology, nine potential effective components, 71 target genes, and 20 pathways were predicted to be involved in RS-mediated regulaton of lipid metabolism disorder. The quantitative analysis suggested that the contents of potential effective components varied among samples from different market places. In conclusion, the presented results provide a chemical basis for further research of Rubus chingii var. suavissimus.